Routing and wavelength assignment for augmented cubes in array-based wavelength-division-multiplexing optical networks. Issue 2 (3rd April 2018) - Li, Tseng-Kuei; Chien, Meng-Jou; Chen, Jheng-Cheng; Tsai, Chang-Hsiung
ABSTRACT: The augmented cube is a class of communication patterns that are employed by a number of typical parallel algorithms. It is one of the hypercube variations, and retains all favourable properties of hypercube. This paper addresses the routing and wavelength assignment (RWA) for the augmented cube communication pattern in a linear array wavelength-division-multiplexing optical network. By using congestion estimation and giving a RWA strategy, we prove that the optimal number of wavelengths is, where N denotes the size of the augmented cube.